Food Barn for The Village Community To Strengthen Community Empowerment Program - Hasmarini, Maulidyah Indira; Purnomo, Didit (Universitas Muhammdaiyah Surakarta, 2016)
This study aimed to assess the achievement level of community empowerment in realizing food security. The result was expected to reveal a model of community empowerment, particularly farmer community institution as an attempt to attain food security. Survey was employed as the research method that involved the farmers (farmer groups) as the members of Food Barn for the Village Community (Lumbung Pangan Masyarakat Desa/LPMD). Technique of rapid rural appraisal was selected in the form of quantitative and qualitative analysis. Preliminary survey in study area was carried out to obtain the characteristic and status of food security; and to mapping the potential and role of Lumbung Pangan Masyarakat Desa in the process of community empowerment. Subsequently, study and analysis was done based on the survey. The results demonstrated the active role of stakeholders (A-B-G-C) was significant in supporting the farmer institution (food barn). The economic and social aspects were also evidenced to have important role in enhancing the farmer community empowerment. This model is called social engine for rural community and local institution, particularly to attain the regional food security.